E-KIDO: The Development of Online Food Ordering System for Primary Schools to Enhance The Quality of Services - Mohd Hatta Mohamed Ali @ Md Hani; Mohammad Haziq Daniel Norazman; Damia Darwisya Abd Rahman; Raja Syairah Najihah Raja Ayub (Multidisciplinary Applied Research and Innovation, 2022)
Coronavirus disease outbreak rapidity is putting administrators in schools to the test. Schools had to shut down during the outbreak, and virtual classrooms had to be implemented. Educational administrators have had to evaluate the types and levels of change required to help teachers and students adapt to new technology and technical abilities. Because of the continuous pandemic, educators and administrators are concerned about the mental health of their employees and students. Students and teachers are putting to the test in a way they have never been before. Standard Operating Procedures (SOP) for physical education students have been amended due to the coronavirus pandemic. The school used various methods to maintain social distance between students, including Telegram, Google Forms, or WhatsApp to take orders of students’ food for recess. As technology has progressed, this way of obtaining meal orders has become outdated. Additionally, this can affect the quality of services the school meals prepared there. Students may now place meal orders more quickly and easily due to the system. A waterfall methodology was used to create this system. The system will include adding to the cart, calculating order totals, and summing up orders. A selection of participants tests the project’s functionality. We found that the system effort had a beneficial effect on school food purchases at the end of the study. Teachers and students can gain from using technology such as this system, making their lives easier and transforming education to the next level.